2018
DOI: 10.1002/ajp.22944
|View full text |Cite
|
Sign up to set email alerts
|

The metabolome as a biomarker of mortality risk in the common marmoset

Abstract: Recently, the common marmoset has been proposed as a non-human primate model of aging. Their short lifespan coupled with pathologies that are similar to humans make them an ideal model to understand the genetic, metabolic, and environmental factors that influence aging and longevity. However, many of the underlying physiological changes that occur with age in the marmoset are unknown. Here, we attempt to determine if individual metabolites are predictive of future death and to recapitulate past metabolomic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The design of the comparative study was based on the difference in lifespans across the Drosophila species and, from the literature, the existence of age-associated metabolic alterations [ 10 , 19 , 20 , 21 , 22 ]. At first, the Drosophila species were grouped into three cohorts according to their life expectancy (long-lived, medium-lived, and short-lived species).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the comparative study was based on the difference in lifespans across the Drosophila species and, from the literature, the existence of age-associated metabolic alterations [ 10 , 19 , 20 , 21 , 22 ]. At first, the Drosophila species were grouped into three cohorts according to their life expectancy (long-lived, medium-lived, and short-lived species).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the dramatic lifespan fluctuation across the species, individuals of different species with similar chronological ages are at various stages of life. In addition, the metabolomic composition of model organisms changes significantly throughout life [ 19 , 20 , 21 , 22 ]. In this case, the hallmarks of aging may be expected to have detectable effects on the metabolome that can prevent a correct selection of relevant metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern supports recent research suggesting that tryptophan metabolism may be an integral part of aging and longevity. High tryptophan (van der Goot and Nollen 2013) and low kynurenine (Sutphin et al 2017) have been shown to promote longevity in worms, and low tryptophan levels were associated with increased risk of mortality in marmosets (Hoffman et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade however, attention has focused more on the details of metabolic regulation which has emerged as a major contributor to the aging phenotype. Metabolomic studies have been increasingly used in both model (e.g., Fuchs et al 2010;Hoffman et al 2014;Houtkooper et al 2011) and non-model (Ball et al 2018;Hoffman et al 2018b;Hoffman et al 2016;Lewis et al 2018;Viltard et al 2019) organisms, leading to the discovery of common conserved pathways associated with aging and longevity. Also, diet as shown by dietary restriction, the most robust method to increase lifespan and health in model organisms, has been found to profoundly modify metabolic regulation (Matyi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation